Perancangan Dan Analisis Struktur Mekanik Prototipe Laser Cutting - Ramadhani, Hafiz; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Laser Cutting machine is a machine that uses a laser beam to cut or carve a particular material. This machine is aimed at small and medium enterprises (UKM) to produce creative products such as decoration, handicrafts, accessories and more. Previously it has been produced some machines that use lasers as cutting tools, but some of the table is very difficult to by UKM, because the price is expensive. In order to fulfill the needs of UKM for cheapest Laser Cutting machines, this research can be obtained Laser Cutting machine with the same function but with an affordable price. In the design process used Autodesk Inventor 2015 software as well as analysis of structural strength in this design. In the analysis process was done with 2 ways, with manual calculations and simulation using Autodesk Inventor 2015. Then from the calculation were results obtained voltage that occurs on the y-axis = 0.21 MPa on the x-axis 1.05 MPa then deflection that occurs on the y-axis = 1.67.10-3 and on the x-axis = 5.9 .10-2. Therefore, in this research is revealed a safe category of machine Laser Cutting machine.Keywords : Laser Cutting machine, stress, deformation